A Descriptive Analysis of Gamification as a Strategy to Enhance Learning Motivation Among Generation Z - Budiyanto, Rachma Marchya; Nur Hidayah, Aqilla Ghina; Hurriatul Muslimah, Zihan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study discusses the use of gamification as a learning strategy to enhance the learning motivation of Generation Z in the midst of the dominance of digital learning environments. The changing characteristics of students, who grow up as digital natives, demand a more interactive and responsive learning approach compared to traditional methods. The aim of this research is to descriptively analyze how Generation Z perceives the elements of gamification and their relationship with learning motivation. This study uses a descriptive quantitative approach and conducts a survey. Data were collected using a Likert scale questionnaire distributed to 26 Generation Z respondents aged 18–22 years, consisting of university students and individuals who have entered the workforce. The research instrument assesses the respondents' views on gamification elements such as feedback, challenges, progress clarity, and reward systems in the context of learning motivation. The results show that Generation Z tends to prefer learning that is interactive and dynamic. Gamification elements such as quick feedback, relevant challenges, and clarity in learning progress are perceived to contribute more to improving concentration, engagement, and understanding of the material compared to symbolic rewards such as points or leaderboards. These findings suggest that the contribution of gamification lies not only in the gaming aspect but also in its ability to create a structured, relevant, and meaningful learning experience. This study is expected to serve as a reference for educators and learning developers in designing gamification strategies that align with the characteristics and learning motivation of Generation Z.